2015
DOI: 10.1007/s11947-015-1604-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combining Pulsed Electric Fields with Maceration Time on Merlot Grapes in Protecting Caco-2 Cells from Oxidative Stress

Abstract: The objective of this study was to investigate the effect of different maceration times (0, 2, 4, 8 and 14 days) after pulsed electric field (PEF) processing (1.5 kV/cm, either at 15 or 70 kJ/kg) on the release of anthocyanins from Merlot grapes (Vitis vinifera) and the bioprotective potentials of grape juice against H 2 O 2 -induced oxidative stress using human intestinal Caco-2 cell culture model. Cell viability, lactate dehydrogenase membrane leakage and nitric oxide production in Caco-2 cells were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Improving the degree of extraction of polyphenols during the maceration-fermentation stage of red winemaking has been one of the most widely investigated applications of pulsed electric fields (PEF) in recent years. Several research groups working with different grape varieties have demonstrated that a PEF treatment applied to grapes before the maceration-fermentation stage allows for a reduction of the contact time of grape skins with the fermenting must, or helps to obtain wines with higher polyphenolic content [2][3][4][5][6]. This effect is attributed to a phenomenon called electroporation, which involves an alteration of cell membrane permeability as a consequence of the application of an external electric field [7].…”
Section: Introductionmentioning
confidence: 99%
“…Improving the degree of extraction of polyphenols during the maceration-fermentation stage of red winemaking has been one of the most widely investigated applications of pulsed electric fields (PEF) in recent years. Several research groups working with different grape varieties have demonstrated that a PEF treatment applied to grapes before the maceration-fermentation stage allows for a reduction of the contact time of grape skins with the fermenting must, or helps to obtain wines with higher polyphenolic content [2][3][4][5][6]. This effect is attributed to a phenomenon called electroporation, which involves an alteration of cell membrane permeability as a consequence of the application of an external electric field [7].…”
Section: Introductionmentioning
confidence: 99%
“…For Yellow Solar carrots, which had a low total carotenoid content, PEF significantly increased the carotenoid content (Leong et al, 2016a;Rezaeinezhad et al, 2022). Leong et al (2016b) also found that PEF treatment shortened the immersion time and improved the protection against H 2 O 2 oxidative stress in Vitis Vinifera. Leong et al also evaluated the effect of PEFs on the release of anthocyanins and the health effects of Pinot noir grape juice; Pinot noir grapes treated with PEF were able to produce substances with stronger antioxidant activity and exhibited greater protection against oxidative stress (Leong et al, 2016c;Chen et al, 2023).…”
Section: Phenols and Carotenoidsmentioning
confidence: 73%